AB0387 Incidence and Risk Factors for Tuberculosis in Japanese Patients with Rheumatoid Arthritis During a 12-Year Observational Period Using the Iorra Cohort. (9th June 2015) - Yamaguchi, R.; Shidara, K.; Tanaka, E.; Inoue, E.I.; Shimizu, Y.; Kobayashi, A.; Sugimoto, N.; Hoshi, D.; Sato, E.; Seto, Y.; Nakajima, A.; Momohara, S.; et al.
Abstract : Background: A high incidence of tuberculosis (TB) in patients with rheumatoid arthritis (RA) has been reported [1]. The incidence of TB has increased with the widespread use of biologics, such as tumor necrosis factor-alpha (TNF-a) [2]; however, there has been no recent increase in the incidence of TB because of the management and screening before initiating biologics [3]. According to our previous report on the incidence of TB in Japanese patients with RA enrolled in the Institute of Rheumatology, Rheumatoid Arthritis (IORRA) cohort, the standardized incidence ratio (SIR) of TB was high [4]; however, the frequency of biologics use is on the rise. Hence, we examined the incidence of TB in RA patients over a long-term period. Objectives: To determine the incidence and risk factors for TB in Japanese RA patients during a 12-year observational period in daily practice. Methods: We established a large observational cohort of RA patients, IORRA cohort in 2000. Among the patients with RA enrolled in the IORRA cohort, all TB cases that developed during the observational period were extracted based on patient self-reporting biannually (at least two times between 2002 and 2013) and confirmed by medical records. We calculated the SIR of TB according to the incidence of TB in the general Japanese population from the Prevention Committee of the Japanese Society for Tuberculosis. Risk factors for TB were examined using a multiple time-dependent Cox regression model. The explanatory variables were age, gender, body mass index, DAS28-CRP, Japanese version of Health Associated Questionnaire, and biologics, methotrexate, and steroid use. Results: Among 10, 415 patients with RA (males, 1, 823; females, 8, 592) with 108, 175 patient-years of follow-up (males, 17, 035; females, 91, 140), 23 TB cases (average age, 56.2 years; RA duration, 8.7 years; males, 32%; steroid use, 56.5% [mean dose =5.0 mg/day]; biologics use, 21.7%; extrapulmonary TB, 43.5%) were confirmed as the cases in this study. Of the 23 TB cases, 5 developed during treatment with biologics (infliximab, 2; etanercept, 2; adalimumab, 1), 2 of 5 cases (infliximab and etanercept, 1 each) developed TB after 9 months of isoniazid (INH) treatment and 1 case (infliximab) developed TB while taking INH. The incidence of TB per 100, 000 patient-years of follow-up was 13.7 (95% CI: 5.5-28.4). The SIRs of TB were 0.85 (95% CI: 0.54-1.27) in all RA patients, 0.84 (95% CI: 0.36-1.66) in males, and 0.85 (95% CI: 0.48-1.40) in females. The risk factors for TB were male (p<0.01), older age (p<0.05), low BMI (p<0.01), and biologics use (p<0.05), although steroid and methotrexate use was not a risk factor. Conclusions: As a result of long-term follow-up (12 years), there was no significant difference in the incidence of TB in Japanese RA patients compared to the general population. Biologics use was a significant risk factor for TB. References: Weisman MT et al., J Rheumatol 2002; 29 (Suppl 65): 33-8. Dixon WG et al., Ann Rheum Dis 2010; 69: 522-8. Sichletidis L et al., Int J Tuberc Lung Dis 2006; 10: 1127-32. Yamada T et al., Ann Rheum Dis 2006; 65: 1661-3. Disclosure of Interest: R. Yamaguchi: None declared, K. Shidara: None declared, E. Tanaka: None declared, E. I. Inoue: None declared, Y. Shimizu: None declared, A. Kobayashi: None declared, N. Sugimoto: None declared, D. Hoshi: None declared, E. Sato: None declared, Y. Seto: None declared, A. Nakajima: None declared, S. Momohara Consultant for: AbbVie, Bristol-Myers-Squibb, Eisai, Mitsubishi-Tanabe, and Takeda, A. Taniguchi Grant/research support from: Takeda, Consultant for: AbbVie, Eisai, Mitsubishi-Tanabe, and Teijin, H. Yamanaka Grant/research support from: AbbVie, Asahikasei Pharma, Astellas, Bristol-Myers-Squibb, Chugai, Daiichi-Sankyo, Eisai, GlaxoSmithKline, Janssen, Mitsubishi-Tanabe, MSD, Nippon Kayaku, Pfizer, Santen, Taisho-Toyama, Takeda, Teijin Pharma, Consultant for: Teijin Pharma, Chugai, Astellas, Bristol-Meyers, AbbVie, Daiichi-Sankyo, Nihon-Kayaku, Mitsubishi-Tanabe, Pfizer, Takeda, UCB